Kebijakan Moneter Islam : Landasan Teoretis, Implementasi, dan Dampaknya Terhadap Stabilitas Ekonomi - Farah Qalbia; M. Reza Saputra (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This research examines Islamic monetary policy, covering its theoretical foundations, implementation in various countries, and its impact and effectiveness. Islamic monetary policy, based on sharia principles such as the prohibition of usury, emphasis on the real sector, and profit-sharing principles, aims to create economic stability and socio-economic justice. Its implementation varies across countries, with some nations fully adopting Islamic financial systems and others using hybrid models. The research method used is a literature review involving the collection, analysis, and synthesis of various secondary sources such as books, journal articles, and relevant research reports. The results show that Islamic monetary policy is effective in controlling inflation, promoting sustainable economic growth, and enhancing financial stability. However, challenges remain in terms of standardizing practices across countries and integration with the global financial system. This study emphasizes the importance of innovation in Islamic financial instruments and increased international cooperation to enhance the effectiveness of Islamic monetary policy in the future.